(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of debt to equity ratio and earnings per share on stock prices. The Unit of Analysis in this research is the construction and building sub sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. This research method uses descriptive and verification methods. The data analysis technique used is multiple linear regression analysis, hypothesis testing using t test and F test. The study population is all construction and building sub sector companies. The study population was all construction and building sub-sector companies listed on the Indonesia Stock Exchange in 2014-2018 as many as 16 companies. By using Purposive Sampling technique obtained 9 companies that match the research sample criteria. Simultaneous research results obtained debt to equity ratio and earnings per share affect the stock price, while the research results partially show the debt to equity ratio and earnings per share have no effect on stock prices.